Off-state leakage current variations in MOSFET mismatch modeling for circuit simulations - Ismail, Muhamad Amri (2007)
MOSFET is a type of field-effect transistor (FET). It has an insulated gate, whose voltage determines the conductivity of the device. This ability to change conductivity with the amount of applied voltage can be used for amplifying or switching electronic signals.